Cross section scaling for the ionization of H2O by highly charged ions - Bachi, Nicolás (2020)
A classical trajectory Monte Carlo model that explicitly considers the ten electrons of the H2O mole cule is used to study electron production in collisions involving bare ions. Present results are contrasted to the reported experimental data and to other theoretical results obtained by means of distorted wave models. Focus is made on the energy range 100 (keV/amu) /ZP-1000 (keV/amu)/ZP along which a simple scaling for the net cross section is introduced.